African music from the point of view of the record industry. From a Special Correspondent of The Star, Johannesburg - Tracey, Hugh (International Library of African Music, 1963)
The key fact in the Bantu record industry is that there are no key facts such as enable experts on the European side to prepare something in accordance with proven formulae and predict its success with reasonable accuracy.Indeed, renowned musicologists after decades of studying Bantu music and customs have been invited to comment on various recordings and the box-office results have conflicted dramatically with their informed opinion. To set against the wealth of evidence that the Bantu record buyer is simply not interested in conventional Western numbers there were the hit sales of The Tennessee Waltz.
Keywords: South Africa; Ethnomusicology; Music; Africa; Black People; African Music; Record Industry